2021
DOI: 10.1038/s41467-021-23469-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potent neutralizing antibodies from convalescent plasma in patients hospitalized for severe SARS-CoV-2 infection

Abstract: In a randomized clinical trial of 86 hospitalized COVID-19 patients comparing standard care to treatment with 300mL convalescent plasma containing high titers of neutralizing SARS-CoV-2 antibodies, no overall clinical benefit was observed. Using a comprehensive translational approach, we unravel the virological and immunological responses following treatment to disentangle which COVID-19 patients may benefit and should be the focus of future studies. Convalescent plasma is safe, does not improve survival, has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
191
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(203 citation statements)
references
References 48 publications
8
191
4
Order By: Relevance
“…The pressing need for treatments for the COVID-19 pandemic obliged the medical community and authorities to embrace the use of convalescent plasma (CP) as a potentially effective and easily accessible form of passive immunotherapy. Despite the rationale for use, and experience in other viral epidemics (1,2), several controlled clinical trials and observational studies have provided inconclusive results regarding the beneficial effects of CP in patients hospitalized for COVID-19 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The evidence suggests that the potential beneficial effects of CP may be limited to the subgroup of non-critical patients who receive high titers of antibodies early in the course of the disease before developing their own humoral immune response (3)(4)(5)(6)(7)(8), or to immuno-compromised oncohematological patients who may fail to mount an effective immune response (9).…”
Section: Introductionmentioning
confidence: 99%
“…The pressing need for treatments for the COVID-19 pandemic obliged the medical community and authorities to embrace the use of convalescent plasma (CP) as a potentially effective and easily accessible form of passive immunotherapy. Despite the rationale for use, and experience in other viral epidemics (1,2), several controlled clinical trials and observational studies have provided inconclusive results regarding the beneficial effects of CP in patients hospitalized for COVID-19 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The evidence suggests that the potential beneficial effects of CP may be limited to the subgroup of non-critical patients who receive high titers of antibodies early in the course of the disease before developing their own humoral immune response (3)(4)(5)(6)(7)(8), or to immuno-compromised oncohematological patients who may fail to mount an effective immune response (9).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we take the impact of the immune response on infection dynamics into account to perform a more robust analysis of different treatment options. Regarding the CP therapy, several studies performed in various countries have shown that this treatment is effective against COVID-19 infections and its safety has been well established in a randomized clinical trial (RCT) on a large population [5,[10][11][12][13][14][15]. However, finding the optimal dose and time for CP therapy is still debated [5].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 4728 records were identified from databases, websites and citation searching. There were 47 studies 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 fulfilled the inclusion criteria and were used for the systematic review and meta‐analysis (Figure 1 ). Of 47 included studies, 21 were clinical trials 16 , 17 , 18 ,…”
Section: Resultsmentioning
confidence: 99%
“…Of 47 included studies, 21 were clinical trials 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 60 , 61 , 62 and 26 were observational studies. 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 55 , 56 , 57 , 58 , 59 Among clinical trials, there were 18 studies published in peer‐reviewed journals 16 , 17 , 18 , 19 , 20 , 21 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation